FUsaM: Framework for Measuring Usability Mobile Applications Based on an SPL - Enríquez, Juan G. (2016)
The widespread use of mobile devices and the heterogeneity of the users involves challenges when evaluating usability of mobile applications. It is important to have methodologies and tools that enable to perform specific usability studies for this type of applications in which the context of use is constantly changing. It is necessary that usability testing are transparent to the user, usability and context data are automatically collected, the test code are not intrusive in the tested application and the tests support the variability of the devices. To achieve the above features, this article presents a framework called FUsaM (Mobile Usability Framework) which is extensible and can generate and integrate usability testing in mobile applications. The design and implementation approach is based on Software Product Line (SPL) combined with Features Oriented Programming (FOP) and Aspect Oriented Programming (AOP). A case study is also presented to prove the functionality.